European biodiversity assessments in livestock science: A review of research characteristics and indicators. (May 2020) - Kok, A.; de Olde, E.M.; de Boer, I.J.M.; Ripoll-Bosch, R.
Highlights: We reviewed scientific literature on effects of livestock on biodiversity in Europe. Analysis focused on general characteristics, indicators used, and the main conclusion. We provide insight in biodiversity assessment of livestock across scales and purposes. Few studies linked livestock to their indirect impacts on biodiversity. Abstract: Developments in agriculture are a main driver for biodiversity loss, in which livestock play a major role through pastures and feed crop cultivation. Addressing biodiversity loss is challenging due to the broad definition of and the multitude of indicators for biodiversity. We reviewed scientific literature assessing effects of livestock on biodiversity in Europe, to provide an overview of general characteristics of these studies and their indicators for biodiversity. The search was performed in SCOPUS and Web of Science and yielded 857 records after deduplication, which was narrowed down to 131 articles that assessed biodiversity impacts of livestock in Europe. Analysis of these articles focused on general characteristics of the research (i.e. context, scale, species, function of livestock, approach), indicators used, and the general conclusion regarding the impact of livestock on biodiversity. The majority of articles studied biodiversity in France, UK, Italy, Germany and Spain; and studied the direct impact of grazing cattle and sheep on biodiversity at field scale. Indirect impacts of livestock on biodiversity through feed production were assessed in few studies. In about one third of the studies, the function of livestock was not related to food production, but to conservation of open landscapes through grazing. We found a large variety of indicators used to assess the impact of livestock on biodiversity. The indicators were divided in seven clusters: 1) DNA, breeds, populations, 2) abundance and richness, 3) traditional diversity indices, 4) novel diversity indices, 5) composition and function, 6) structure and habitats, and 7) qualitative scoring systems. The majority of studies included the indicators abundance and richness, although studies differed in the plant or animal species studied. Indicators used differed across scales and between functions of livestock. Studies with a conservation function of livestock more often used indicators from clusters 5 and 6 than studies with a food production function. A positive impact of livestock on biodiversity was often found in studies with a conservation function, whereas a negative impact of more intensive livestock was often found in studies with a food production function. The identified indicators for biodiversity were connected to different assumptions and values, and therefore answer different questions and present different conclusions regarding the state of biodiversity. This review provides insight in biodiversity assessments of livestock across scales and purposes; highlights that few studies linked livestock to their indirect impacts on biodiversity; and stresses that one should be critical about the indicators used for biodiversity.